PENGEMBANGAN ALAT PRAKTIKUM MESIN ATWOOD - Rohmah, Kholifatur; Partono, Partono; Salim, M. Barkah (Universitas Muhammadiyah Metro, 2021)
Abstract: The development of science and technology increasingevolved following the times, especially in education. Education thatcannot be separated from the learning process requires a tool that canhelp and support the learning process. One of them is physics learningwhich requires a tool that can show physical phenomena in real. Basedon the above ideas then developed atwood machine practicum tool thatcan be used in learning. The purpose of this study is to: (1) Increase thelevel of accuracy of atwood machine tools. (2) Produce appropriateatwood machine tools. (3) Knowing the feasibility level of the developedatwood machine tool. (4) Knowing the respondent's response to atwoodmachine tool developed. The type of this research is the development ofADDIE model which consists of 5 stages: analysis, design, development,implementation, and evaluation. Based on the research result: (1) thequality atwood machine tool obtaine the average percentage accordingto the media expert of 92% with very reasonable criteria, and accordingto the material expert of 91% with very reasonable criteria. The averagepercentage of experts is 91.5% with very reasonable criteria means thatpracticum tool can be used in learning. (2) The result of questionnaire ofstudent response got percentage 87% with criteria strongly agree thatstudent have interest to atwood machine tools in. Suggestion in thisresearch that atwood machine practice tool can be used and used forlearning process and practice tool can be developed become moresophisticated.Keywords: Development, Practicum Tools, Atwood Machines.